Wireless xbee-based energy meter monitoring system - Muhammad Hasbullah, Idris (2012)
In this project, automatic meter reading (AMR) has been studied. Automatic meter reading (AMR), is the technology of automatically collecting consumption, diagnostic, and status data from water meter or energy metering devices (gas, electric) and transferring that data to a central database for billing, troubleshooting, and analysing. This technology mainly saves utility providers the expense of periodic trips to each physical location to read a meter. Another advantage is that billing can be based on near real-time consumption rather than on estimates based on past or predicted consumption. AMR technologies include handheld, mobile and networktechnologies based on telephony platforms (wired and wireless), radio frequency (RF), or power line transmission. For this study, AMR system in the form of handheld device has been developed. PIC Microcontroller unit has been used to continuously monitors and records the energy meter reading in its EEPROM. The meter reading will be sent to another microcontroller unit (handheld device) wirelessly to be displayed on LCD display. For transmission of data from the energy meter to the handheld device, XBee RF module has been used. Two XBee modules have been used in this project. The XBee modules have been used as RF transceiver to transmit and receive the energy meter reading. Result of this project is the meter reading displayed at both the sending-end LCD and receiving-end LCD.